Surface Area Analysis of Activated Carbon Material From Palm Frond Waste using Different Activation Agents - Sahara Hamas Intifadhah; Rahmawati Munir; Dadan Hamdani; Adrianus Inu Natalisanto; Suhadi Muliyono (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2025)
Carbon is one of the abundant elements obtained from organic matter, one of which is found in the fronds of oil palm trees which is found on the Kalimantan Island. This research uses local organic waste in East Kalimantan to be used as activated carbon material, palm frond waste. Activated carbon material is one of the materials that has a high surface area and is widely applied for adsorbent materials. This study aims to analyze and compare the surface area of activated carbon synthesized from palm frond waste using different activating agents. This research also analyzes the nature of the material structure, surface area, pore size and pore volume of activated carbon. The method used is the process of thermal activation and chemical activation to convert carbon into activated carbon with variations of activating agents, phosphoric acid (H3PO4) and sodium hydroxide (NaOH). XRD, BET-SAA and SEM-EDX characterization tests were conducted. The results obtained show that the amorphous structure of activated carbon has been formed and there is an increase in BET surface area due to the activation process. The surface area obtained for the Non-Activated Carbon (C) sample is 15,149 m2/g, Activated Carbon-NaOH (AC-1) is 2,082 m2/g, Activated Carbon-H3PO4 (AC-2) is 307,692 m2/g. This shows that the best sample with the highest surface area is the AC-2 sample which uses the H3PO4 chemical activator solution.